Chemical characterization of stabilized and carbonized polyacrylonitrile (pan) fibers treated with oleic acid. - Salleh, S.N.M. (EDP Sciences, 2014)
Polyacrylonitrile (PAN) fiber is the best precursor for carbon fibers due to high carbon content after heat treatment. After the polymer was spun into fibers, the fibers will undergo pretreatment process with chemical solution known as post spinning treatment. Post spinning will directly affect conversion of PAN fiber to carbon fiber. Oleic acid was used as post spinning treatment chemical solution to PAN fibers. The pretreated PAN fiber will be heated at 250°C and 800°C. The fibers were studied using Fourier Transform Infra-Red (FTIR), X-ray Photoelectron Spectroscopy (XPS) and DSC to study the chemical change during heat treatment. PAN fibers treated with oleic acid have reduced the cyclization energy and increase oxygen and carbon content leading to high performance carbon fibers. © 2014 Owned by the authors, published by EDP Sciences.